Nar-A-Viz: A methodology to visually extract the narrative structure of text. (September 2019) - Dessavre, Dante Gama; Ramirez-Marquez, Jose E.
Highlights: Created a new model of narrative structure quantifying message delivery in documents. Created a new visualization analytics for narrative structure. Showed visual analytics can summarize contents of a speech and identify structural analysis. Developed system for speech comparison and analysis with political speeches. Abstract: Being able to tell and understand stories is a key component for efficient communications. The narrative structure is the structural framework that underlies the order and manner in which this story is presented to a reader, listener, or viewer, this work presents a novel visualization methodology that can be used to extract the narrative structure of texts and present in a visual, immediate and intuitive manner. This tool efficiently summarizes the content of a text, and it also allows in depth analysis of the narrative structure. The characteristics and use of the tool are exemplified using a TED talk by Hans Rosling. Its potential then is shown using two historical speeches: President Donald Trump's inaugural speech and I Have a Dream by Dr. Martin Luther King Jr.